Characterization and Metabolism Effect of Seed Endophytic Bacteria Associated With Peanut Grown in South China - Li, Limei; Zhang, Zhi; Pan, Shiyu; Li, Ling; Li, Xiaoyun (Frontiers in Microbiology, 2019)
Endophytes are considered to be excellent biocontrol agents and biofertilizers, and are associated with plant growth promotion and health. In particular, seed-endophytic bacteria benefit the host plant’s progeny via vertical transmission, and can play a role in plant growth and defense. However, seed-associated endophytic bacteria have not been fully explored, with very little known about how they interact with peanut (Arachis hypogaea), for example. Here, 10 genera of endophytic bacteria were isolated from the root tips of peanut seedlings grown either aseptically or in soil. Forty-two bacterial colonies were obtained from peanut seedlings grown in soil, mostly from the genus Bacillus. Eight colonies were obtained from aseptic seedling root tips, including Bacillus sp., Paenibacillus sp., and Pantoea dispersa. Four Bacillus peanut strains GL1–GL4 (B.p.GL1-GL4) produced bio-films, while B.p.GL2 and Paenibacillus glycanilyticus YMR3 (P.g.YMR3) showed strong amylolytic capability, enhanced peanut biomass, and increased numbers of root nodules. Conversely, P. dispersa YMR1 (P.d.YMR1) caused peanut plants to wilt. P.g.YMR3 was distributed mainly around or inside vacuoles and was transmitted to the next generation through gynophores and ovules. Hexanoate, succinate, and jasmonic acid (JA) accumulated in peanut root tips after incubation with P.g.YMR3, but linolenate content decreased dramatically. This suggests that strain P.g.YMR3 increases JA content (14.93-fold change) and modulates the metabolism of peanut to facilitate nodule formation and growth. These findings provide new insight into plant–seed endophytic bacterial interactions in peanut.